Carbon-coated fluorinated graphite for high energy and high power densities primary lithium batteries - Zhang, Qi; D'Astorg, S.; Xiao, Pengfei; Zhang, X.; Lu, Li (Elsevier Science B.V., Amsterdam., 2010)
The electrochemical performances of fluorinated graphite have been improved by coating a uniform carbon layer on commercial CFx (x = 1) powder used as cathode material in lithium battery. In comparison with the cell using un-coated CFx as cathode, the cell using carbon coated CFx cathode has a higher energy density and higher power density, particularly at higher discharge current rates (1C above). This is because the conductive carbon coating provides the exterior connectivity between particles for facile electron conduciton, resulting in high rate performance.
Keywords: Primary lithium batteries; Fluorinated graphite; Carbon coating; Electrochemistry; Discharge